2020
DOI: 10.1002/jsfa.10962
|View full text |Cite
|
Sign up to set email alerts
|

Determination of acid value during edible oil storage using a portable NIR spectroscopy system combined with variable selection algorithms based on an MPA‐based strategy

Abstract: BACKGROUND:The acid value is an important indicator for evaluating the quality of edible oil during storage. This study employs a portable near-infrared (NIR) spectroscopy system to determine the acid value during edible oil storage. Four MPAbased variable selection methods, namely competitive adaptive reweighted sampling (CARS), the variable iterative space shrinkage approach (VISSA), iteratively variable subset optimization (IVSO), and bootstrapping soft shrinkage (BOSS) were introduced to optimize the prepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Moisture content plays an important role in reflecting the quality and stability of foods and TCMs [ 17 , 18 ]. Storage conditions with high moisture content are beneficial for the growth of microbes, leading to the production of more free fatty acids and even unpleasant odor [ 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moisture content plays an important role in reflecting the quality and stability of foods and TCMs [ 17 , 18 ]. Storage conditions with high moisture content are beneficial for the growth of microbes, leading to the production of more free fatty acids and even unpleasant odor [ 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…An atmospheric compensation of ethanol was combined with the PCA method by feature extraction to identify different brands of goods, as well as to assess the degree of food spoilage. Hui et al [ 51 ] used a portable NIR spectroscopy system to determine the acidity of edible oils during storage and compared four variable selection methods (CARS, VISSA, IVSO, and BOSS) to optimize the NIR spectral data, and obtained support from vector machine models for different selection methods. The BOSS method yielded the lowest number of characteristic wavelengths.…”
Section: Application Of Infrared Spectroscopy Technology In Detection...mentioning
confidence: 99%
“…From this, it is shown that the machine learning algorithm represented by SVM performs better than the PLSR algorithm to predict the alpha-pinene content in nutmeg fruits using Vis-NIR spectra data. If it is observed from the RPD parameters in alpha-pinene estimation modeling using Vis-NIR spectral data, it has been better than the model built by Jiang et al [32] to estimate the acid value of oil using portable NIRs.…”
Section: Calibration Model For Prediction Alpha-pinenementioning
confidence: 99%